Evaluating the Feasibility and Efficacy of a Dual-Modality Nanoparticle Contrast Agent (Nanotrast-CF800) for Image-Guided Sentinel Lymph Node Mapping in the Oral Cavity of Healthy Dogs - Wan, Jennifer; Oblak, Michelle L.; Ram, Ann S.; McKenna, Charly; Singh, Ameet; Nykamp, Stephanie (Frontiers in Veterinary Science, 2021)
A combination of pre- and intraoperative sentinel lymph node (SLN) mapping techniques have been suggested to optimize SLN detection. A novel liposomal nanoparticle, Nanotrast-CF800 (CF800), utilizes computed tomography lymphography (CTL) and near infrared fluorescence imaging (NIRF) for image-guided surgery and SLN mapping. This novel tracer agent has not been evaluated in companion animals. The objective of this study was to evaluate the feasibility and efficacy of CF800 for SLN mapping in the oral cavity of healthy dogs and to report any local adverse effects. Six healthy adult purpose-bred research dogs randomly received either 1 mL (group 1) or 2 mL (group 2) of CF800 injected into the submucosa at the level of the right canine maxillary tooth. CTL and percutaneous NIRF were performed at 1, 3, and 10 minutes, then 1, 2, 4, 7, and 10 days post-injection (p.i). Overall, both CTL and NIRF identified SLNs in all dogs. The overall peak mean contrast enhancement of the SLNs was 73.98 HU (range 63.45-86.27 HU) at 2 days p.i. Peak fluorescence of the SLN occurred at 1 day p.i. The agent was retained within the SLN for at least 7 days for CTL and 4 days for NIRF. No adverse effects were observed. Local administration of CF800 was simple and feasible for the detection of SLNs using CTL+NIRF in the head and neck of healthy dogs and was not associated with significant local adverse events.